2003
DOI: 10.1046/j.1525-1446.2003.20204.x
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent Health Promotion Scale: Development and Psychometric Testing

Abstract: The purpose of this study was to assess the psychometric properties of a newly devised instrument, the Adolescent Health Promotion scale (AHP), a 40-item Likert-type self-report instrument used to detect unhealthy lifestyles in adolescents. Content validity was considered to be supported based on the findings of previous studies and the observations of a panel of 14 content experts. This study examined the construct validity and reliability of the instrument. The psychometric properties of the AHP, including i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
137
2
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 135 publications
(160 citation statements)
references
References 11 publications
5
137
2
14
Order By: Relevance
“…4 On the other hand, a study in Turkey with 1,351 male and female adolescents between the ages of 11 and 19 demonstrated that there were statistically significant differences in terms of gender and age concerning the frequency of healthpromoting behaviors. Adolescent girls presented higher scale mean scores of health-promoting behaviors than boys.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…4 On the other hand, a study in Turkey with 1,351 male and female adolescents between the ages of 11 and 19 demonstrated that there were statistically significant differences in terms of gender and age concerning the frequency of healthpromoting behaviors. Adolescent girls presented higher scale mean scores of health-promoting behaviors than boys.…”
Section: Introductionmentioning
confidence: 99%
“…3 Programs aimed at preventing unhealthy lifestyles and risk behaviors are more effective when implemented in early life. 4 A positive health culture promotes higher levels of health literacy, aiding young people to deal with determinants of health and allowing them to develop the cognitive and social competencies needed for maintaining good health levels. 6 Health promotion and disease prevention are essential for reducing the need for health care among young people.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations